1996
DOI: 10.1074/jbc.271.26.15510
|View full text |Cite
|
Sign up to set email alerts
|

Asn102 of the Gonadotropin-releasing Hormone Receptor Is a Critical Determinant of Potency for Agonists Containing C-terminal Glycinamide

Abstract: We demonstrate a critical role for Asn102 of the human gonadotropin-releasing hormone (GnRH) receptor in the binding of GnRH. Mutation of Asn102, located at the top of the second transmembrane helix, to Ala resulted in a 225-fold loss of potency for GnRH. Eight GnRH analogs, all containing glycinamide C termini like GnRH, showed similar losses of potency between 95- and 750-fold for the [Ala102]GnRHR, compared with wild-type receptor. In contrast, four GnRH analogs that had ethylamide in place of the C-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 24 publications
4
65
1
Order By: Relevance
“…With regard to LH, the sensitivity to mGnRH was higher than to cGnRH-II because it elicited a significant response at a concentration 100 times lower. The similar potency of mGnRH and cGnRH-II is in contrast to that observed in other systems [28, 47], but is in agreement with the high binding affinity of cGnRH-II for the GnRH receptor in humans [48]. Millar et al [49]have shown that a cGnRH-II receptor is expressed in gonadotropes and appears to modulate the type I (mGnRH) receptor and the secretion of LH and FSH.…”
Section: Discussioncontrasting
confidence: 47%
“…With regard to LH, the sensitivity to mGnRH was higher than to cGnRH-II because it elicited a significant response at a concentration 100 times lower. The similar potency of mGnRH and cGnRH-II is in contrast to that observed in other systems [28, 47], but is in agreement with the high binding affinity of cGnRH-II for the GnRH receptor in humans [48]. Millar et al [49]have shown that a cGnRH-II receptor is expressed in gonadotropes and appears to modulate the type I (mGnRH) receptor and the secretion of LH and FSH.…”
Section: Discussioncontrasting
confidence: 47%
“…The chicken GnRH receptor that we have cloned exhibits marked pharmacological differences in its interaction with GnRH agonist and antagonist analogs and has sequence differences from the mammalian receptors that may be used to identify functional residues. 3.32(121) residues in the chicken GnRH receptor is expected, as these residues are believed to interact with the amino-(Glu(P) 1 -His 2 ) and carboxyl-terminal (Gly 10 -NH 2 ) residues of the GnRH ligands, which are conserved in the native mammalian and chicken forms of GnRH (9,11,12). As expected from biological assays, the chicken GnRH receptor does not distinguish between its cognate native ligand, [Gln 8 ]GnRH (K i 5.3 Ϯ 0.5 nM), and mammalian GnRH (K i 4.1 Ϯ 1.2 nM).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular modeling and site-directed mutagenesis studies have been extensively applied to delineate ligand binding sites in the GnRH receptors (Sealfon et al, 1997;Millar et al, 2004Millar et al, , 2007 and other GPCRs (Ballesteros et al, 2001;Lu et al, 2002 (Zhou et al, 1995;Flanagan et al, 2000); Tyr 5 interacts with Tyr 290(6.58) ; Arg 8 of GnRH I interacts with Asp 302(7.32) (Flanagan et al, 1994;Fromme et al, 2001); and Gly 10 NH 2 with Asn 102(2.65) (Davidson et al, 1996;Hoffmann et al, 2000).…”
Section: Discussionmentioning
confidence: 99%